(untitled) (FULafia Journal of Science and Technology, 2020)
Transmission rate and bit error rate (BER) performance are two important parameters for ultra-wideband (UWB) communication system. Among the widely used modulation schemes, pulse position modulation (PPM) is attractive for its high energy efficiency. However, PPM scheme suffers low data rate and poor bit error rate performance due to the symbol pattern (duration) required for high number of M bits. The study employed combination of Spatial Pulse Position Modulation (SPPM) and On-Off-Keying (OOK) in order to improve the BER performance. While SPPM results in high bit error rate performance, the OOK is predicted to improve the BER at low signal to noise Ratio (SNR). The enhanced scheme combined SPPM and OOK, results has an improved BER by an order of two and an increase in the data rate by two orders of magnitude relative to the standard PPM. The study revealed that two schemes could be combined to enhanced transmission rate and low SNR. The scheme could be recommended optical communication system (OCS).